Population structure of Albizia niopoides (Benth.) Burkart and Mimosa hexandra Micheli (Fabaceae) in the Brazilian Chaco - Baptista, Mozart Sávio Pires; Assunção, Vivian Almeida; Seleme, Elidiene Priscila; Sartori, Ângela Lúcia Bagnatori (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The objective of the present study was to verify the existence of variation in the population structure of Albizia niopoides (Benth.) Burkart and Mimosa hexandra Micheli among and within forested remnants of Chaco. The study was carried out in two forested remnants of Chaco, where four plots of 2,500 m² each were established, two plots in each remnant forest. For the analysis of the population structure, height and diameter of all individuals of the studied species were recorded. There was a difference in the population structure of Albizia niopoides and Mimosa hexandra in the Chaco flood plain, due mainly to the height of the individuals, both inside and between the remnants. The prevalence of individuals of smaller diameter class showed that the population is self-regenerative and the environment is heterogeneous, probably due to seasonal flooding. Luminosity is possibly a factor that contributes to the structuring of the population of the two species, since they are forest trees.
Keywords: Trees; Fabaceae; Phytosociology; Phenology